Connectivity, interoperability and manageability challenges in internet of things - Haseeb, Shariq; Hassan Abdalla Hashim, Aisha; Khalifa, Othman Omran; Ismail, Ahmad Faris (American Institute of Physics, 2017)
he vision of Internet of Things (IoT) is about interconnectivity between sensors, actuators, people and processes. IoT exploits connectivity between physical objects like fridges, cars, utilities, buildings and cities for enhancing the lives of people through automation and data analytics. However, this sudden increase in connected heterogeneous IoT devices takes a huge toll on the existing Internet infrastructure and introduces new challenges for researchers to embark upon. This paper highlights the effects of heterogeneity challenges on connectivity, interoperability, management in greater details. It also surveys some of the existing solutions adopted in the core network to solve the challenges of massive IoT deployment. The paper finally concludes that IoT architecture and network infrastructure needs to be reengineered ground-up, so that IoT solutions can be safely and efficiently deployed.